A French Jesuit in China: The Case of André Yverneau 1948–1951 - Baycroft, Timothy (Religions, 2024)
During the many centuries of interaction and exchange between China and Europe, one of the most complex and ambiguous relationships was that of the Catholic Church and its missionaries in China. On one hand, they contributed to and can be seen as a part of the European imperial project of world colonisation, but on the other hand, they were instrumental in sharing and exchanging knowledge, as well as creating schools and other institutions in the places they created missions. At the same time, attempts were being made within the Catholic Church to promote the development of a Chinese clergy, although this issue remained divisive. This article examines these complex relationships through the eyes of a French Jesuit, André Yverneau, who was in China between 1948 and 1951 and who left a collection of letters back to his family describing these years. His experiences, observations, reactions and attitudes towards China and the mission are presented and analysed in order to re-evaluate some of the main debates surrounding the mission in China in the mid-twentieth century: education, language, indigenisation, and politics, both internal to the Catholic Church and with its relations in China.